Integrating Creative Dance for Character Development in Early Childhood Education - Ardiyanti, Dhea; Jayadinata, Asep Kurnia; Muqodas, Idat (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
Although the importance of character building in early childhood is widely recognized, practical strategies for integrating it into daily learning remain underexplored. This study aims to examine the integration of creative dance into Early Childhood Education (PAUD) as a structured approach to character development, explored through the lens of learning planning and evaluation. Creative dance, as part of the creative arts, offers a developmentally appropriate approach to fostering social, emotional, and moral competencies. Using a qualitative case study approach, this research involved PAUD teachers implementing creative dance across six learning stages: warming up, exploring, skill development, creating, forming, and presenting. Each stage was analyzed for its potential to cultivate character values, including discipline, responsibility, tolerance, self-confidence, and cooperation. The findings suggest that creative dance can effectively support character development when implemented through planning and continuous evaluation. Its success largely depends on teachers’ ability to align activities with children’s developmental needs. This study highlights the need for targeted teacher training and institutional support to optimize the potential of creative dance in early childhood character education.